Development of cold-formed steel moment-resisting connections with bolting friction-slip mechanism for seismic applications. (August 2019) - Shahini, Marzie; Sabbagh, Alireza Bagheri; Davidson, Paul; Mirghaderi, Rasoul
Abstract: This paper presents an investigation into a friction-slip mechanism in bolted joints in cold-formed steel (CFS) moment-resisting connections suitable for seismic areas. The aim is to achieve higher ductility and energy dissipation capacity through an appropriately designed bolted connection, enabling activation of bolt slip, acting as a fuse mechanism, postponing the initiation of non-ductile local buckling in the CFS beams. By means of validated finite element analysis (FEA), both monotonic and cyclic performance of CFS connections comprising two types of square (SB) and circular (CB) bolt group arrangements, with four types of beam sections, are studied comparatively without and with slip at various levels. It is shown that the connections with slip provide higher energy dissipation capacity by up to 75% compared with that of the connections without slip. A design approach to predict an appropriate level for the connection slip moments to be initiated before the beam buckling moment is introduced using the direct strength method (DSM). On comparing the bolt forces obtained for the SB and CB groups, the CB connections produce a more uniform bolt-group force distribution which is closer to the idealised method; while the SB connection encounter a significant delay of up to 30% in activation of bolt group slip which could lead to unfavourable beam local buckling. Furthermore, to avoid an unfavourable hardening effect due to the bolts bearing action, slotted holes are used with a recommended length obtained for the cyclic movements of the bolts in the range of the designed connections. The instantaneous centre of rotation results show that the connections with slip have less deviation from the idealised centre of rotation than the connections without slip. Highlights: Bolting friction-slip mechanism can improve ductility and energy dissipation capacity of CFS moment-resisting connections. Circular bolting arrangement provides a more uniform bolt-group force distribution than the square bolting arrangement. Connections with slip shows less deviated instantaneous centre of rotation than the connections without slip. Slotted bolt holes can delay unfavourable bearing action of bolts and its consequential local buckling in the beam. DSM can be used to predict the beam buckling in moment-resisting connections and to help set the connection slip level.